Voltammetric Responses of Surface-Bound and Solution-Phase Anthraquinone Moieties in the Presence of Unbuffered Aqueous Media - Batchelor-McAuley, C; Kozub, B; Menshykau, D; Compton, R (2011)
The voltammetry of solution-phase redox species involving proton transfer are known to be qualitatively altered under conditions of nonbuffered media (Quan, M. et al. J. Am. Chem. Soc. 2007, 129, 12847-12856). We now report first the voltammetric response of solution-phase anthraquinone monosulphonate on a gold macroelectrode in the presence of a limited concentrations of protons; further we provide quantitative analysis of the voltammetry under unbuffered conditions whereby it is possible to demonstrate through simulation that in some conditions the pH at the electrode may alter by up to 5-6 pH units as compared to that of the bulk solution. This change in local environment adjacent to the electrode is caused by the consumption of protons during the electrochemical process. As a result, in conditions of low buffering the electrochemical reduction is limited by the availability of protons, leading to a measured voltammetric signal with two voltammetric waves. Second the work is developed through the study of an anthraquinone modified pyrolytic graphite electrode under conditions of finite proton concentration. We demonstrate experimentally how analogous split wave results occur for surface confined species. These results provide physical insight into the consumption of protons during the electrochemical process and highlight how methods of pH measurement based upon the use of redox modified electrode surfaces are nonpassive. © 2010 American Chemical Society.